Uterine Inversion; A case report - Bouchikhi, C (CoAction Publishing, 2008)
The puerperal uterine inversion is a rare and severe complication occurring in the third stage of labour. The mechanisms are not completely known. However, extrinsic factors such as oxytocic arrests after a prolonged labour, umbilical cord traction or abdominal expression are pointed. Other intrinsic factors such as primiparity, uterine hypotonia, various placental localizations, fundic myoma or short umbilical cord were also reported. The diagnosis of the uterine inversion is mainly supported by clinical symptoms. It is based on three elements: haemorrhage, shock and a strong pelvic pain. The immediate treatment of the uterine inversion is required. It is based on a medical reanimation associated with firstly a manual reduction then surgical treatment using various techniques. We report an observation of a 25 years old grand multiparous patient with a subacute uterine inversion after delivery at home.